2016
DOI: 10.1902/jop.2016.150587
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Status in Morbidly Obese Patients With and Without Obstructive Sleep Apnea Syndrome Risk: A Cross‐Sectional Study

Abstract: There was no association between periodontal disease and OSAS risk in Class III obese patients, but OSAS risk was associated with both NC and PPNC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…75,76 However, further studies are necessary to understand the role of obesity as a confounding factor. 77 Also, studies to the effect of treatment of OSA on periodontal disease and vice versa are required.…”
Section: Dentist's Role In Obstructive Sleep Apnoeamentioning
confidence: 99%
See 1 more Smart Citation
“…75,76 However, further studies are necessary to understand the role of obesity as a confounding factor. 77 Also, studies to the effect of treatment of OSA on periodontal disease and vice versa are required.…”
Section: Dentist's Role In Obstructive Sleep Apnoeamentioning
confidence: 99%
“…Periodontal disease shares some of these mechanisms, and recent studies have shown a significant association with OSA 75,76 . However, further studies are necessary to understand the role of obesity as a confounding factor 77 . Also, studies to the effect of treatment of OSA on periodontal disease and vice versa are required.…”
Section: Obstructive Sleep Apnoea: the Dentist's Rolementioning
confidence: 99%
“…Adipose cells secrete bioactive molecules (adipokines) such as leptin, adiponectin, visfatin and resistin that are elevated in obese individuals (Luo and Blackledge 2018). These cells also secrete elevated inflammatory cytokines such as TNF-α, IL-6, and other bioactive molecules including inhibitor of plasmogen activator-1 (PAI-1, involved in vascular homeostasis), angiotensinogen (ANG, regulators of blood pressure), vascular endothelial growth factor (VAGF, promotor of angiogenesis) and acute phase C-reactive protein (CRP) (Sales-Peres et al 2016). Leptin is thought to be a key regulator of innate and adaptive immunity and thus enhances obesity-associated and inflammatory diseases that affect bones and joints (Francisco et al 2018).…”
Section: Impact Of Obesity On the Immune Responsementioning
confidence: 99%
“…Obstructive sleep apnea additionally leads to daytime symptoms of functional impairment, such as impaired alertness (Young et al 1993;Tanaka and Shima 2010). Sleep apnea syndrome is associated with general health complications, including cardiovascular disease, hypertension, and diabetes mellitus, as well as oral complications, such as periodontitis (Elmasry et al 2000;Peppard et al 2000;Shahar et al 2001;Tanigawa et al 2004;Sales-Peres et al 2016). The Epworth sleepiness scale (ESS) is a representative self-reported questionnaire that consists of 8 items for measuring human daytime sleepiness.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have already investigated the relationships between oral status and ESS scores. For instance, a research group reported finding no association between the ESS score and periodontal status in morbidly obese patients (Sales-Peres et al 2016). In addition, another group reported that patients with burning mouth syndrome, a chronic disease characterized by a burning sensation and pain in the oral cavity, exhibited significant decreases in the ESS score, as compared with a healthy control group (Lopez-Jornet et al 2015).…”
Section: Introductionmentioning
confidence: 99%